Future Pathways of Water, Energy, and Food in the Eastern Nile Basin - Ahmed Abdelkader; Amin Elshorbagy; Mohamed Elshamy; Howard Wheater (Earth's Future)
Abstract The Eastern Nile Basin (ENB) countries of Egypt, Sudan, South Sudan, and Ethiopia are subject to pronounced water, energy, and food (WEF) insecurity. There is a need to manage the WEF nexus to meet rapidly increasing demands, but this is extremely challenging due to resource scarcity and climate change. If countries that rely on shared transboundary water resources have contradictory WEF plans, that could diminish the expected outcomes, both nationally and regionally. Egypt as the most downstream Nile country is concerned about ongoing and future developments upstream, which could exacerbate Egypt's water scarcity and affect its ability to meet its WEF objectives. In this context, we introduce a multi‐model WEF framework that simulates the ENB water resources, food production, and hydropower generation systems. The models were calibrated and validated for the period 1983–2016, then utilized to project a wide range of future development plans, up to 2050, using four performance measures to evaluate the WEF nexus. A thematic pathway for regional development that shows high potential for mutual benefits is identified. However, the WEF planning outcomes for the region are sensitive to climate change, but, if social drivers could be managed (e.g., by lowering population growth rates) despite the difficulties involved, climate change impacts on WEF security could be less severe.